Vegetation colonization and biodiversity dynamics on the exposed Aral Sea bed: A 35 years investigation - Bekhzod Adilov; Khabibullo Shomurodov; Tashkhanum Rakhimova; Azamat Sultamuratov; Farrukh Polvonov; Gulnora Begjanova; Zafarjon Jabbarov; Lei Wang; Zhenyong Zhao (Ecological Indicators)
The Aral Sea, formerly a large saltwater lake in Central Asia, has almost disappeared due to unsustainable water management practices. This desiccation has resulted in a profound ecological catastrophe, characterized by the emergence of vast, barren landscapes. This study investigates the dynamics of vegetation colonization and biodiversity on the desiccated Aral Sea bed, focusing on the interplay of soil gradations, plant species composition, and the development of distinct ecosystem types. Over a 35-years investigation period, 30 dominant species were identified across five ecosystem types: ephemeral ecosystems, wasteland ecosystems, post-ecosystems, remnant ecosystems, and neo-ecosystems. Community analysis revealed generally low similarity between these ecosystem types, with significant floristic overlap observed only between ephemeral and neo-ecosystems (41.4 %) and between neo-ecosystems and post-ecosystems (54.1 %). An ecological scale was developed, categorizing 65 distinct ecotypes based on soil mechanical composition, salinity levels, and groundwater depths; this framework revealed clear patterns in species dominance and biodiversity distribution. Considerable variability in soil factors was evident across the study area. Gradients in mechanical composition and salinity significantly impacted vegetation cover and the activity of dominant species. Higher vegetation activity was generally associated with sandy soils (clay content less than 10 %) and lower salinity (<4.0 g/L). Groundwater levels exhibited varied effects on vegetation, with the highest vegetative cover typically observed where groundwater was at a depth of 1.0–1.5 m. Regression models and canonical correspondence analysis highlighted the strong influence of soil gradations on the differentiation of ecosystem types, indicating a dynamic interplay between prevailing soil conditions and the processes of species colonization. The study concludes that ecosystem development on the desiccated Aral Sea bed is shaped by complex interactions among various soil factors and underscores the critical importance of considering landscape-scale interference and heterogeneity in understanding vegetation succession patterns.